2012
DOI: 10.4021/jnr145e
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Role of Thiamine in Parkinson’s Disease: Preliminary Report

Abstract: Elmer This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The effective determination of vitamins has been done by various analytical techniques, the main of which are chromatographic techniques (HPLC, Ionic chromatography, supercritical fluid chromatography coupled/not coupled with mass spectrometry, etc. ), spectroscopic techniques (fluorescence, UV spectroscopy), immunochemical methods, chemiluminescence, chromatography-mass spectrometry (GC-MS), gas chromatography, and many others [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Although these techniques have applications in many fields, they have complicated sample processing, are time consuming, and require expensive equipment.…”
Section: The Vitaminsmentioning
confidence: 99%
“…The effective determination of vitamins has been done by various analytical techniques, the main of which are chromatographic techniques (HPLC, Ionic chromatography, supercritical fluid chromatography coupled/not coupled with mass spectrometry, etc. ), spectroscopic techniques (fluorescence, UV spectroscopy), immunochemical methods, chemiluminescence, chromatography-mass spectrometry (GC-MS), gas chromatography, and many others [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Although these techniques have applications in many fields, they have complicated sample processing, are time consuming, and require expensive equipment.…”
Section: The Vitaminsmentioning
confidence: 99%
“…It had previously been shown that free thiamine levels are decreased in the CSF of patients with Parkinson's disease compared with control patients 61 . Moreover, a very recent preliminary clinical study reported the beneficial effects of thiamine treatment (100-200 mg daily doses of parenteral thiamine) on a limited number of patients 62 . This again needs confirmation.…”
Section: Thiamine In Stress Diabetes and Neurodegenerative Diseasesmentioning
confidence: 99%